The discontinued traditions of malay wood carvings in modern and post-modern architecture in Malaysia : a failure to develop the discourse on ornamentation in architectural works - Mohamad Rasdi, Mohamad Tajuddin (Faculty of Buit Environment, 2006)
The main intention of this paper is to contribute some thoughts on why the tradition of wood carvings in traditional Malay architecture was discontinued at the rise of modern and post-modern architectural works in Malaysia. Although the tradition of wood carvings more or less came to a stop in public architectural works with the development of colonial architecture, this paper seeks to clarify the modernistic and post-modern arguments on the problem or issues of ornamentation. I propose that the main reason why traditional wood carvings never became part of mainstream modern and post-modern architecture and is relegated to the elitist works of palaces and hotels or resorts is because architects, artists and intellectuals in Malaysia failed to develop a working discourse on ornamentation in architecture. Although modernism mainly or seemingly rejected the use of ornaments, there was still a strong strand of its development in the architecture of Frank Lloyd Wright. The western post-modernist architects such as Michael Graves and Charles Jencks went on to develop a discourse on ornamentation under the area of architectural meaning and linguistics.